The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.virol.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence variation among isolates of monkey B virus ( Macacine alphaherpesvirus 1) from captive macaques

Abstract: Complete genome sequences of 19 strains of monkey B virus (Macacine alphaherpesvirus 1; BV) isolated from several macaque species were determined. A low level of sequence variation was present among BV isolates from rhesus macaques. Most variation among BV strains isolated from rhesus macaques was located in regions of repetitive or quasi-repetitive sequence. Variation in coding sequences (polypeptides and miRNAs) was minor compared to regions of non-coding sequences. Non-coding sequences in the long and short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 43 publications
(59 reference statements)
0
24
0
Order By: Relevance
“…MG266707) shared 100% identity with 9 previously sequenced isolates collected from captive NHPs (rhesus macaques and a Japanese macaque [ M. fuscata ]) and an isolate originating from primate kidney cells (Figure). The coding sequences obtained from all 3 samples were highly similar (98.3%–100%) to sequences generated from laboratory strains of McHV-1 originating from captive rhesus macaques ( 29 ). …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…MG266707) shared 100% identity with 9 previously sequenced isolates collected from captive NHPs (rhesus macaques and a Japanese macaque [ M. fuscata ]) and an isolate originating from primate kidney cells (Figure). The coding sequences obtained from all 3 samples were highly similar (98.3%–100%) to sequences generated from laboratory strains of McHV-1 originating from captive rhesus macaques ( 29 ). …”
Section: Resultsmentioning
confidence: 72%
“…KY628985), isolated from a captive bonnet macaque ( M. radiata ), and strain 16293 (GenBank accession no. KY628972; Figure), isolated from a captive rhesus macaque ( 29 ). The US5 sequence generated from the third positive swab specimen differed at a single nucleotide, which resulted in an amino acid change from aspartic acid to glycine at position 28 (nt 84) of the coding region of the gJ gene.…”
Section: Resultsmentioning
confidence: 99%
“…These captive transmissions, especially between macaque species can complicate phylogenetic analysis. In particular, cross-species transmission appears to be fairly common among the core herpes B strains, and has been discussed previously in depth by Eberle et al [12]. In some of the herpes B strains, the original source of the virus appears to be unclear.…”
Section: Host-virus Co-speciationmentioning
confidence: 79%
“…Pathogenicity is one determinative method in which there appears to be a difference between the Pig and Lion-tailed macaque viruses and the remaining herpes B strains. Studies performed by Eberle et al examining the lethal dose (LD 50 ) of the sequenced herpes B strains in mice showed that the Pig and Lion-tailed macaque simplex viruses had different lethality phenotypes compared to the remaining herpes B strains [12]. Importantly, the LD 50 values for the Pig and Lion-tailed viruses were >10 7 PFU, while the average for the remaining herpes B strains was approximately 10 4 PFU.…”
Section: Cryptic Viral Speciesmentioning
confidence: 99%
See 1 more Smart Citation